American Nonprofit Law in Comparative Perspective - Alyssa A. Dirusso (Washington University Global Studies Law Review, 2011)
The article presents a comparative law which explores approaches to nonprofit regulations in several countries in Europe and Asia. It discusses the basic laws for the nonprofit sector in the U.S. and is then contrasted with the approach for nonprofit laws in other countries. It explores the two distinctive themes of the American nonprofit regulations, which is its difference in primary relational focus and its property of being unusually tax-centric in its regulatory scheme.
Keywords: Comparative law; Nonprofit organizations -- Law & legislation; International law -- Interpretation & construction; Nonprofit sector; Law -- United States -- Interpretation & construction